Effect of Quick Ratio, Total Asset Turnover, and Receivable Turnover on Return on Assets in Food and Beverages Companies Listed on the Indonesia Stock Exchange (IDX) - Muhammad Yamin Siregar; Mardiana Mardiana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine the effect of Quick Ratio, Total Asset Turnover and Receivable Turnover on Return On Assets in Food & Beverages companies listed on the Indonesia Stock Exchange (IDX). The research applied is an associative type with the aim of knowing the effect of one variable on another. The data used is secondary data with multiple linear regression analysis method panel data using the help of the Eviews10 programs. The population applied in this study is the Food & Beverages companies listed on the Stock Exchange with a total of 26 companies and the sample in this study amounted to 8 companies. The data collection technique used is documentation. The results of the study prove that partially the QR variable has a significant effect on ROA, the TATO variable has a partial but not significant effect on ROA and the RTO variable has no effect on return on assets. Simultaneously quick ratio, total asset turnover and receivable turnover has no effect on ROA. With the coefficient of determination (R²) of 0.094563.